2012
DOI: 10.3732/ajb.1100531
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a first set of polymorphic microsatellite markers in saffron, Crocus sativus (Iridaceae)

Abstract: The microsatellite markers reported here will be useful for evaluating genetic diversity and will likely serve as an ideal resource for use in marker-assisted breeding programs, germplasm analysis, and varietal identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 10 publications
1
16
1
Order By: Relevance
“…The average PIC value was 0.38 ranging from 0.1 to 0.54 (Table 2). Nemati et al (2012) observed that a total of 27 alleles with a mean of 2.60 per locus and the mean of PIC across all loci varied from 0.1 to 0.54 with an average of 0.34 in their SSR analysis, which is apparently compatible with our present results. Moreover, our results showed a new set of 12 polymorphic microsatellite loci out of 15 monomorphic microSaffron (Crocus sativus L.), a monomorphic or polymorphic species?…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The average PIC value was 0.38 ranging from 0.1 to 0.54 (Table 2). Nemati et al (2012) observed that a total of 27 alleles with a mean of 2.60 per locus and the mean of PIC across all loci varied from 0.1 to 0.54 with an average of 0.34 in their SSR analysis, which is apparently compatible with our present results. Moreover, our results showed a new set of 12 polymorphic microsatellite loci out of 15 monomorphic microSaffron (Crocus sativus L.), a monomorphic or polymorphic species?…”
Section: Discussionsupporting
confidence: 92%
“…sativus as cultivated crocus is a sterile species with distinct morphological and growing characterisSaffron (Crocus sativus L.), a monomorphic or polymorphic species? 757 (Siracusa et al, 2012;Erol et al, 2014) and SSR (Rubio-Moraga et al, 2009;Nemati et al, 2012), the actual genetic diversity present in C. sativus is still an open question. In this study, 27 microsatellite markers were tested to measure level of polymorphism and investigated the genetic relationship and structure among Iranian Crocus ecotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A further six primer pairs were designed for simple sequence repeats from sequences of C. sativus registered in GenBank (NCBI) (Nemati et al 2012). Primer sequences and individual annealing temperatures for each primer pair used are shown in Table 2.…”
Section: Ssr-primer-designmentioning
confidence: 99%